Integrating Batak Dalihan Na Tolu Values in Christian Character Education within Family Context - Sanjay Nadeak (Fakultas Keguruan dan Ilmu Pendidikan Kristen IAKN Palangka Raya, 2026)
Character education is a fundamental aspect of human development, particularly within the Christian educational context, where moral formation is inseparable from biblical teachings. This study examines how the Batak cultural philosophy of Dalihan Na Tolu can be integrated into family, based Charistian character education. Employing a qualitative literature review approach, the research analyzes twenty validated sources, including scholarly journals and books, to explore the interplay between local cultural values and Christian moral formation. Findings indicate that the principles of Dalihan Na Tolu, namely, somba marhula-hula, manat mardongan tubu, and elek marboru, resonate with Christian virtues such as respect, responsibility, and relational harmony, and can effectively complement family, based character education. Integrating these local values within a Christian framework provides a contextualized and culturally sensitive approach to character formation, enabling families to cultivate virtues aligned with both cultural norms and biblical principles. This study contributes to thr discourse on contextualized Christian education by demonstrating how indigenous cultural systems can reinforce moral and spiritual development in family settings.